Polyamine Oxidase-Generated Reactive Oxygen Species in Plant Development and Adaptation: The Polyamine Oxidase-NADPH Oxidase Nexus - Péter Benkő; Katalin Gémes; Attila Fehér (MDPI AG, 2022)
Metabolism and regulation of cellular polyamine levels are crucial for living cells to maintain their homeostasis and function. Polyamine oxidases (PAOs) terminally catabolize polyamines or catalyse the back-conversion reactions when spermine is converted to spermidine and Spd to putrescine. Hydrogen peroxide (H2O2) is a by-product of both the catabolic and back-conversion processes. Pharmacological and genetic approaches have started to uncover the roles of PAO-generated H2O2 in various plant developmental and adaptation processes such as cell differentiation, senescence, programmed cell death, and abiotic and biotic stress responses. Many of these studies have revealed that the superoxide-generating Respiratory Burst Oxidase Homolog (RBOH) NADPH oxidases control the same processes either upstream or downstream of PAO action. Therefore, it is reasonable to suppose that the two enzymes co-ordinately control the cellular homeostasis of reactive oxygen species. The intricate relationship between PAOs and RBOHs is also discussed, posing the hypothesis that these enzymes indirectly control each other's abundance/function via H2O2.